Nitrogen Potassium and Nitrogenpotassiumsulfur Containing Complex Fertilizers on the base of Melt Ammonium Nitrate, Potassium Chloride and Phosphogypsum - Abdurasul Mamataliyev, Doniyor Sherkuziev, Boris Beglov, Shafoat Namazov (International Journal of Advanced Science and Technology, 2020)
For the purpose of modification of ammonium nitrate, reduce its risk of explosive properties studied the process of obtaining on its base nitrogenpotassiumsulfur containing complex fertilizers by additive to its melt potassium chloride, produced by Dehkanabad plant of potassium fertilizers and phosphogypsum, which is the waste product of extraction of phosphoric acid, which is waste product of extraction of phosphoric acid at Almalyk JSC "Ammophos-Maxam".  The composition and properties of obtaining fertilizers were defined. The main criteria of modification is-strength of granules. Strength of pure ammonium nitrate granules is 1.6 MPa, strength of granules obtaining on ratio N: K2O = 1: 0.5 and additive with 10% phosphogypsum is 7.65 MPa.